Implantação do mapeamento de processos em uma organização sem fins lucrativos - Budke, Daiara Amanda (2023)
In today's dynamic environments, organizations are relentlessly searching for ways to improve their operational performance. In this scenario, an approach that stands out for its effectiveness is the adoption and implementation of process mapping. This method not only offers a comprehensive and structured view of a company's operations, but also proves to be a fundamental step in optimizing business efficiency. In this context, this work aims to evaluate the impact of implementing process mapping in a non-profit organization, through studies and the development of a methodology that meets the particularities of the organization in question. The results obtained through this particular work highlighted process mapping as a highly valuable tool for managing the operational structure and this methodology not only improved process efficiency, but also contributed positively to organizational culture, increasing productivity and quality of the work performed.